Reference Range of Fetal Transverse Cerebellar Diameter Between 18 and 24 Weeks of Pregnancy in a Brazilian Population. (February 2015) - Araujo Júnior, Edward; Martins, Wellington P.; Nardozza, Luciano Marcondes Machado; Pires, Claudio Rodrigues; Filho, Sebastião Marques Zanforlin
To determine a reference range of fetal transverse cerebellar diameter in Brazilian population. This was a retrospective cross-sectional study with 3772 normal singleton pregnancies between 18 and 24 weeks of pregnancy. The transverse cerebellar diameter was measured on the axial plane of the fetal head at the level of the lateral ventricles, including the thalamus, cavum septum pellucidum, and third ventricle. To assess the correlation between transverse cerebellar diameter and gestational age, polynomial equations were calculated, with adjustments by the determination coefficient (R 2 ). The mean of fetal transverse cerebellar diameter ranged from 18.49 ± 1.24 mm at 18 weeks to 25.86 ± 1.66 mm at 24 weeks of pregnancy. We observed a good correlation between transverse cerebellar diameter and gestational age, which was best represented by a linear equation: transverse cerebellar diameter: –6.21 + 1.307*gestational age (R 2 = 0.707). We determined a reference range of fetal transverse cerebellar diameter for the second trimester of pregnancy in Brazilian population.